Pengaruh Tingkat Pendidikan Orang Tua Terhadap Motivasi Belajar Siswa Kelas V SDN Japanan II Gudo Jombang: Pengaruh Tingkat Pendidikan Orang Tua Terhadap Motivasi Belajar Siswa Kelas V SDN Japanan II Gudo Jombang - Aulia, Naflah; Rochmania, Desty Dwi (IJPSE Indonesian Journal of Primary Science Education, 2025)
The research was motivated by the lack of motivation to learn in class V students at SDN Japanan II Gudo. The aim of this research is to determine whether there is an influence of parental education level on the learning motivation of class V students at SDN Japanan II Gudo Jombang. The type of research used is descriptive quantitative. This research was conducted at SDN Japanan II, Gudo District, Jombang Regency with the sample used being twenty-seven fifth grade students. The data collection method used in this research was questionnaires and documentation. The result of the research show that there is a moderate influence between the level of parental education on students learning motivation. In other words, the level of parental education has a contribution to the parents, the higher the student’s learning motivation. Vice versa, the lower the parent’s education level, the lower the student’s learning motivation.